PEOPLE’S ORİENTATİON IN POLAND TOWARDS THE EUROPEAN UNION - Hakan Samur (Ankara Avrupa Çalışmaları Dergisi)
I f the European Union is to achieve its ultimate aim o f becoming a fully-fledged political community (the ideal o f ever closer union)ş it must be supported, alongside legal-institutional advances, by the development o f a common and sufficient orientation tovvards the Union among itsconstituent citizens. This article attempts to show if (and what şort of) an orientation had been developed during the pre-membership period o f a new member tate, Poland. The results are not encouragingtovvards the ideal o f political community, and demonstrate the negative and retarding impact o f the recent enlargement o f the Union. Examination o f people’s orientation towards the EU in the pre-membership stage o f Poland seems to have specifically anteresting and useful Information for the reader in Turkey that will start EU membership talks this year after a long period o f wait.